Effects of ketone bodies on endurance exercise - Samsone, M.; Samsone, A.; Borrione, P.; Romanelli, F.; Di Luigi, L.; Sgro, P. (Current Sports Medicine Reports, 2018)
Priorities for every athlete include improving endurance performance, optimizing training, nutrition, and recovery. Nutritional strategies are crucial to support athletes to perform at the highest level, and considering that muscular and hepatic glycogen stores are limited, alternative strategies to maximize fat metabolism have been suggested. A ketogenic diet has been proposed as a possible method of providing metabolic fuel during prolonged periods of exercise. However, clinical trials and empirical experience have produced contrasting results regarding the ergogenic value of a ketogenic diet. For this reason, using ketone esters and/or salts have been proposed to obtain nutritional ketosis without limiting carbohydrate intake. Exogenous ketones should not only represent an alternative metabolic fuel source, sparing carbohydrates, but they also may increase postexercise glycogen replenishment, decrease proteolysis, and act as metabolic modulators and signaling metabolites. While there are some encouraging results showing an increase in endurance performance, contrasting evidence regarding the efficacy of exogenous ketones for endurance performance is present and further studies should be performed to make a definitive statement.